The Impact of Digital Archiving on Document Management Efficiency in the Directorate of Service and Zones Investment Planning, Ministry of Investment and Downstreaming /BKPM - Eka Yulianti; Veithzal Rivai Zainal; Azis Hakim (Dinasti Review, 2025)
Every institution or agency in the execution of daily administrative activities is inseparable from the process of records management, as archives essentially serve as documentation or records of all activities conducted. These records act as authentic evidence that may be required at any time, yet their storage is often overlooked or undervalued. The digital era has brought significant transformation to archival systems, changing how organizations, agencies, and individuals including at the Directorate of Services and Zones Investment Planning, Ministry of Investment and Downstream Industry/BKPM help organizations store, manage, and access information. In this regard, digital archiving has become a transformative solution in document management, replacing conventional paper-based systems. This study aims to analyze the impact of digital archiving on document management efficiency, covering aspects such as access speed, cost savings, and data security. The research method adopts a qualitative approach through systematic literature review and analysis of secondary data from credible sources. The findings indicate that digital archiving significantly enhances efficiency through automation, reduction of physical storage space, and improved document security. Therefore, digital archiving encourages organizations to adopt digital systems to boost productivity, sustainability, and efficiency in document management.